Relationships between internal facilitation processes and implementation outcomes among hospitals participating in a quality improvement collaborative to reduce cesarean births: a mixed-methods embedded case study - Jennifer A. Callaghan-Koru; Rachel Blankstein Breman; Bonnie DiPietro; Loren Henderson; Geoffrey Curran (Implementation Science Communications)
Abstract Background Quality improvement collaboratives (QICs) are a common strategy for implementing evidence-based practices; however, there is often variable performance between participating organizations. Few studies of QICs assess the internal facilitation (IF) processes engaged in by participating organizations, which may be key to understanding and enhancing the effectiveness of QICs as an implementation strategy. We examined IF processes among hospitals participating in Maryland’s perinatal QIC to implement national guidelines for reducing primary cesarean births. Methods This study followed a mixed-methods embedded case study design. We conducted qualitative interviews with internal implementation leaders at 21 QIC-participating hospitals using a guide informed by the iPARIHS and CFIR frameworks. Two investigators independently coded transcripts in Dedoose using a modified CFIR codebook including seven IF process codes adapted from published categorizations. The investigators also independently applied the CFIR rating system to rate each IF process as a barrier (-2, -1), facilitator (+ 1, + 2), neutral (0), or mixed (X), for each hospital. Final ratings were established through consensus discussions. Average ratings were calculated by hospital and process and charted alongside implementation outcomes from secondary data sources for identification of patterns. Results Hospital leaders engaged in a variety of activities within each IF process. The average hospital rating across IF processes ranged from -1.1 to + 1.5. The IF process with the highest average rating was project management (average: 1.0; SD: 0.9), the lowest was planning (average: 0.5; SD: 1.0) and the most variable was providing individual support and accountability (average: 0.5; SD: 1.2). Negative ratings resulted from hospital teams not engaging in an IF process or the activities of hospital teams being insufficient to overcome related contextual barriers. Average IF process ratings were significantly higher among hospitals that implemented more than the median number of practice changes. Multiple contextual determinants influenced each IF process; work infrastructure and relational connections were the most frequent influences across IF processes. Conclusions IF processes played an important role in determining implementation success at hospitals participating in a perinatal QIC. Monitoring and strengthening IF processes at participating organizations may enhance the effectiveness of QICs as an implementation strategy.